Implementasi Fungsi Manajemen dalam Meningkatkan Pelayanan Kepada Calon Jamaah Haji - Mirawati, Mirawati; Sarbini, Ahmad; Sadiah, Dewi; Soleh, Soleh (Mabrur: Academic Journal of Hajj and Umra, 2022)
This study aims to determine the implementation of management functions in the form of planning, organizing, mobilizing, and monitoring carried out at the Integrated Hajj and Umrah Service Center (PLHUT) Bekasi Regency in improving services to prospective pilgrims. The method used in this study is a descriptive method with a qualitative approach which aims to describe and provide an explanation of the implementation of management functions in improving services. Data obtained through observation, interviews, and documentation studies. From the exposure of the research results, it can be seen that in improving services to prospective pilgrims at PLHUT Bekasi Regency, they have implemented work principles based on management functions which include planning, organizing, mobilizing, and supervising, but in the implementation there are still obstacles that occur both from internal and external